Dynamic tensile fracture of liquid copper containing helium bubbles. (15th October 2022) - Jiang, Dong-Dong; Zhou, Ting-Ting; Wang, Pei; He, An-Min
Highlights: Strain rate effect of tensile damage of liquid Cu containing He bubbles is studied. The strain rate-dependent damage mechanism of Cu-He system is first discovered. He bubbles only reduce the tensile strength of liquid Cu when ε ˙ < 3.0×10 10 /s. The first mechanical model of dynamic tensile damage of Cu-He system is developed. Abstract: The dynamic tensile fracture process of liquid copper containing helium bubbles system is systematically investigated by molecular dynamics simulations and theoretical modeling. A strain rate-dependent damage mechanism that transforms from a co-growth of voids and helium bubbles to a sole expansion of helium bubbles as the strain rate decreases is firstly found, and a corresponding physical explanation is proposed. Meanwhile, it is found that the dynamic tensile strength of the material is significant affected by the transition of the damage mechanism. Based on the revealed damage mechanism and the basic properties of helium bubbles such as internal pressure and surface tension obtained with the help of molecular dynamics simulations, a mechanical model is constructed to describe the dynamic damage process of the system. The volume evolution of each helium bubble as well as stress evolution of the system obtained from molecular dynamics simulations is well reproduced by the mechanical model in a wide range of strain rate. The strain rate-dependent damage mechanism and the proposed theoretical damage model will provide insights into understanding the dynamic responses of metals containing initial bubbles under extreme conditions. Graphical abstract: Image, graphical abstract